Endoscopic en bloc resection of an esophageal leiomyoma - Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2014)
No Abstract Available DOI: http://dx.doi.org/10.3126/jaim.v3i1.10700 Journal of Advances in Internal Medicine 2014;03(01):28-29